Exogenous application of calcium ameliorates salinity stress of mungbean - Khan, Haider Iqbal; Ghosh, Totan Kumar; Mia, Md Abdul Baset (Annals of Bangladesh Agriculture, 2023)
An experiment was conducted to investigate the impact of exogenous Ca in alleviating salinity stress of mungbean. Two mungbean genotypes, BD 6895 and BD 6905, were used with four different Ca levels (5, 10, 15 and 20 mM) under 10 dSm-1 salinity conditions in a hydroponic culture. The application of exogenous Ca positively influenced on overall plant growth and development. Although both genotypes exhibited similar plant heights, they gave the peak (56.65 and 48.6 cm for BD 6895 and BD 6905, respectively) at 10 mM Ca. Higher levels of exogenous Ca were associated with increased chlorophyll content. Maximum Chlorophyll (1.6 mg g-1) was observed at 15 mM Ca treatment. Furthermore, exogenous Ca application reduced Malondialdehyde levels (at 15 mM Ca: 1.14 and 1.69 μmole/g for BD 6895 and BD 6905, respectively). Both the genotypes exhibited a proline content pattern, demonstrating proline content upsurge with increased Ca application. Microscopic analysis revealed larger vascular areas with exogenous Ca (BD 6895: 402 µm, BD 6905: 398.3 µm) compared to smaller areas under salinity stress (BD 6895: 258.7 µm, BD 6905: 248.4 µm). Salinity stress induced changes in upper epidermis thickness, leaf tissue compactness, chloroplast breakdown and chlorosis in mungbean plants. However, exogenous Ca application counteracted these detrimental effects, enabling mungbean plants to thrive in saline conditions. In conclusion, the study highlights the positive influence of exogenous Ca (10-15 mM) in promoting mungbean growth and managing salt stress. Ann. Bangladesh Agric. (2023) 27 (2): 91-104